Leveraging asynchronous speaking tasks to promote willingness and confidence to speak in Spanish: A qualitative study - Jaramillo, Nadia (Australasian Journal of Educational Technology, 2021)
This study describes the experiences of students in a flipped intermediate Spanish college class who used a video discussion digital tool to develop their confidence to speak in the foreign language. Students participated in a series of 10 speaking tasks designed based on the framework on technology-mediated tasks (Gonzalez-Lloret & Ortega, 2014) and the world-readiness standards for communicative performance of the American Council on the Teaching of Foreign Languages (2015). Through semi-structured interviews and reflection journals, students shared their learning accomplishments, unveiled their inner fears in speaking skills and detailed their journey in gaining confidence to speak in Spanish. Their experiences showed that willingness to communicate and self-efficacy are driving forces that, fostered in a brave learning environment, enable students to take risks and be creative with the language. The study also presents pedagogical implications regarding the design of technology-mediated tasks and the conditions of the learning environment that can foster or hinder students’ language oral communicative skills. Implications for practice or policy: Technology-mediated tasks should be designed based on a learner-centred approach and the affordances of the tool to promote communicative competence in foreign and second language learning. Technology-mediated tasks can promote the development of confidence to use the foreign and second language more spontaneously, while allowing students to fail without being judged or penalised. Technology-mediated tasks can give students some control over their own learning process, facilitating opportunities for self-monitoring to gain confidence in speaking in the foreign or second language.